Diversifying but not Integrating: Entropic Measures of Local Segregation. (2nd March 2018) - Kramer, Rory; Kramer, Peter
Abstract: Scholars of segregation have struggled to adapt indices designed to model two‐group segregation for cities with large populations drawn from more than two racial/ethnic groups. Considering segregation as a social form of entropy resolves that struggle and introduces a family of related measures that offer means of analysing segregation at both the local (neighbourhood) level and the greater (city/region) area. A case study of Philadelphia's level of segregation from 1990 to 2010 illustrates the benefits of the new measures. While Philadelphia has diversified, it remains racially segregated. Further, the new measures show the growing importance of Hispanic segregation and a shift from segregation being visited upon the city's Black residents to being driven by a White population that grows more segregated as its population share shrinks. Integrating measures of segregation and diversity into studies of residential racial patterns enhances our understanding of racial segregation patterns in a multiracial context.